2014
DOI: 10.1111/grs.12058
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and variation in North American orchardgrass (Dactylis glomerata L.) cultivars and breeding lines

Abstract: Orchardgrass (Dactylis glomerata L.) is a high quality forage grass naturalized to temperate climates. Used extensively in hay and grazing agriculture, hundreds of orchardgrass cultivars have been released over the past 50 years. However, progress in yield and other agronomic characteristics in orchardgrass cultivars has occurred slowly and often inconsistently. One cause of the slow progress could be a lack of genetic diversity among orchardgrass cultivars, or an over‐abundance of diversity within cultivars. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Xie et al. () reported tentative and unsupported groupings in 52 cultivars and breeding lines of orchardgrass. Last et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al. () reported tentative and unsupported groupings in 52 cultivars and breeding lines of orchardgrass. Last et al.…”
Section: Discussionmentioning
confidence: 99%
“…AFLP analysis by Tuna et al (2004) suggested a high level of gene flow among natural orchardgrass populations in the Thrace region of Turkey. Xie et al (2014) reported tentative and unsupported groupings in 52 cultivars and breeding lines of orchardgrass. Last et al (2013) reported a high degree of gene flow leading to low genetic distance among individuals and populations between two Swiss ecotype populations of orchardgrass that were less than 100 km apart.…”
Section: Genetic Diversity and Population Structurementioning
confidence: 99%
“…More recent public orchardgrass germplasm improvement work in the United States focused on the development of nonflowering populations (Casler et al, 2013, 2014), with little documentation of other objectives. While a number of commercial cultivars from private programs are available in North America, much of this is based on the recycling of older cultivars rather than the incorporation of novel germplasm (Xie et al, 2014a). The work reported in this paper complements ongoing efforts to identify and develop new sources of orchardgrass germplasm for use in temperate agriculture (Robins et al, 2012a; 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Paiute). However, cultivar performance under different or stressed conditions has been inconsistent [9], possibly due to a lack of uniformity in orchardgrass cultivars [10,11] or the unpredictability of appropriate environmental conditions in field settings [12]. Improving forage production and quality under abiotic stresses are objectives in orchardgrass breeding and genetics programs throughout the world (e.g., [13]).…”
Section: Introductionmentioning
confidence: 99%